Epidemiological Study of Hospital-Acquired Bacterial Conjunctivitis in a Level III Neonatal Unit - Catarina Dias; Márcia Gonçalves; Anabela João (The Scientific World Journal)
Background. Conjunctivitis is one of the most frequently occurring hospital-acquired infections among neonates, although it is less studied than potentially life-threatening infections, such as sepsis and pneumonia. Objectives. The aims of our work were to identify epidemiologic characteristics, pathogens, and susceptibility patterns of bacterial hospital-acquired conjunctivitis (HAC) in a level III neonatal unit. Materials and Methods. Data were collected retrospectively from patient charts and laboratory databases. Hospital-acquired conjunctivitis was defined in accordance with the Centers for Disease Control/National Healthcare Safety Network (CDC/NHSN) diagnostic criteria. Results. One or more episodes of HAC were diagnosed in 4,0% () of 1492 neonates admitted during the study period. Most of the episodes involved premature (75,4%) and low birth weight (75,4%) neonates. Infection rates were higher among patients undergoing noninvasive mechanical ventilation (46,7%), parenteral nutrition (13,6%), and phototherapy (6,8%). Predominant pathogens included Serratia marcescens (27,9%), Escherichia coli (23%), and Pseudomonas aeruginosa (18%). Susceptibility patterns revealed bacterial resistances to several antibiotic classes. Gentamicin remains the adequate choice for empirical treatment of HAC in our NICU. Conclusion. It is important to know the local patterns of the disease in order to adjust prevention strategies. Our work contributes to the epidemiological characterization of a sometimes overlooked disease.